Gene Expression and Protein Synthesis in Mitochondria Enhance the Duration of High-Speed Linear Motility in Boar Sperm - Zhu, Zhendong; Umehara, Takashi; Okazaki, Tetsuji; Goto, Masaaki; Fujita, Yoko; Hoque, S. A. Masudul; Kawai, Tomoko; Zeng, Wenxian; Shimada, Masayuki (Frontiers in Physiology, 2019)
Sperm motility patterns are continuously changed after ejaculation to fertilization in the female tract. Hyperactivated motility is induced with high glucose medium in vitro or the oviduct fluids in vivo, whereas sperm maintain linear motility in the seminal plasma or the uterine fluids containing low glucose. Therefore, it is estimated that sperm motility patterns are dependent on the energy sources, and the mitochondrial oxidative phosphorylation is activated to produce ATP in low glucose condition. To elucidate these hypotheses, boar sperm was incubated in different energy conditions with the transcription and translation inhibitors in vitro. Sperm motility parameters, mitochondrial activity, ATP level, gene expression and protein synthesis were analyzed. Sperm progressive motility and straight-line velocity were significantly increased with decreasing glucose level in the incubation medium. Moreover, the mitochondrial protein turnover meaning transcription and translation from mitochondrial genome in sperm is activated during incubation. Incubation of sperm with mitochondrial translation inhibitor (D-chloramphenicol) suppressed mitochondrial protein synthesis, mitochondrial activity and ATP level in sperm and consequently reduced the linear motility speed, but not the motility. Thus, it is revealed that the mitochondrial central dogma is active in sperm, and the high-speed linear motility is induced in low glucose condition via activating the mitochondrial activity for ATP generation.